THE EFFECTS OF MENOPAUSE AND AGING ON HYPERTENSION AND DEGENERATIVE DISEASES: HYPERTENSION AND GDS COUNSELING AND SCREENING - Dewi, Ni Nyoman Sri Artina; Aningsih, Baharika Suci Dwi; Simaibang, Frenta Helena (LPPM Univ. Ibn Khaldun Bogor, 2025)
Menopause is a natural biological phase in women that is characterized by the cessation of the menstrual cycle due to a decrease in the hormones estrogen and progesterone. A decrease in this hormone has implications for an increased risk of hypertension and degenerative diseases such as diabetes and osteoporosis. This phenomenon is also seen in the elderly in RW 07, Tanah Tinggi Village, Central Jakarta, with a prevalence of hypertension of 48.8% and diabetes mellitus of 16.3%. This community service aims to increase the knowledge and awareness of the elderly about the effects of menopause, the risk of hypertension, degenerative diseases, and provide health screening in the form of blood pressure, cholesterol, and blood sugar checks during (GDS). The activity was held on July 11, 2025 with 82 elderly participants aged 40–72 years. The material was delivered through lectures and interactive discussions by supervisors and students, with PPT and leaflet media. Knowledge evaluation using pre-test and post-test was carried out on 35 participants who completed the questionnaire. The results showed an increase in the average score from 6.1 to 8.5, indicating an increase in understanding of educational materials. It also provides free health screening, allowing for early detection of the risk of degenerative diseases. The results of this service are in line with the literature that states that community-based education is effective in improving health literacy for the elderly. The combination of education and health screening has proven to be the right strategy for preventing complications of degenerative diseases....